Discoordination of labor activity: theory and practice - G. R. Kozonov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article presents the literature review of current conception of development, etiology, pathogenesis, clinical manifestations and management of discoordination in labor activity. Special attention is payed to the clinical course of the labor and its outcome and for morhpofunctional features of the myometrium in this category of patients.